Macrozoobenthos diversity at Istana Amal Beach, Penajam Paser Utara Regency, East Kalimantan - Zabila, Mariana Afna; Adnan; Suryana, Irma (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
Istana Amal Beach, located in Penajam Paser Utara, East Kalimantan, is one of the region's ecotourism destinations. One of the key indicators of environmental quality in this area is the presence of macrozoobenthos. This study, conducted in December 2023, aimed to identify the types of macrozoobenthos present, calculate the diversity, evenness, and dominance indices, and assess the physical and chemical parameters of the water at Istana Amal Beach. A purposive sampling method was applied at two stations, selected based on different activity types in the area. The results revealed the presence of macrozoobenthos from two classes: Gastropoda and Bivalvia, comprising a total of 16 species. The ecological index values indicated a moderate diversity (H' = 2.2), high evenness (E = 0.8), and low dominance (D = 0.1), suggesting a relatively balanced ecosystem. Water quality measurements at both sampling points showed a salinity of 30 ppt, pH averaging 7.65, temperature of 30°C, and dissolved oxygen levels averaging 5.2 mg/L. The substrate at the site was identified as having a sandy texture.